2022
DOI: 10.5005/jp-journals-10071-23950
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sedation and Analgesia during Noninvasive Ventilation: Systematic Review of Recent Evidence and Recommendations

Abstract: A bstract Aim This systematic review aimed to investigate the drugs used and their potential effect on noninvasive ventilation (NIV). Background NIV is used increasingly in acute respiratory failure (ARF). Sedation and analgesia are potentially beneficial in NIV, but they can have a deleterious impact. Proper guidelines to specifically address this issue and the recommendations for or against it are scarce in the literature. In the most recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…13 A significant amount of NIV patients need sedation on order to improve mask and ventilation tolerance, otherwise, nurses will spend extra time at the patient's bedside in order to fix these problems constantly. 15 Although we measured an increased time for monitoring and assistance of the patients during NIV, the overall NAS in NIV patients is lower compared to IMV because several other factors are compensating. Looking at nursing workload as a whole, not just at this one component, different authors have stated that NIV is equally, 8,11 or sometimes less burdensome than IMV for the nursing staff.…”
Section: Discussionmentioning
confidence: 91%
“…13 A significant amount of NIV patients need sedation on order to improve mask and ventilation tolerance, otherwise, nurses will spend extra time at the patient's bedside in order to fix these problems constantly. 15 Although we measured an increased time for monitoring and assistance of the patients during NIV, the overall NAS in NIV patients is lower compared to IMV because several other factors are compensating. Looking at nursing workload as a whole, not just at this one component, different authors have stated that NIV is equally, 8,11 or sometimes less burdensome than IMV for the nursing staff.…”
Section: Discussionmentioning
confidence: 91%
“…The authors concluded that before considering sedation, the clinician should attempt nonpharmacological strategies (e.g. reassurance, orientation, environmental measures), followed by ventilator/interface optimisation [66 ▪ ]. Dexmedetomidine is a frequent choice - given the pharmacological profile and preservation of airway protection and respiratory drive.…”
Section: Troubleshooting Common Problemsmentioning
confidence: 99%
“…There is good quality evidence that the use of analgosedation is associated with improved NIV tolerance and reduced risk of invasive mechanical ventilation. 4 , 5 While the use of sedation or analgesia alone is beneficial, their combined use is associated with increased NIV failure. 6 An ideal analgo-sedative drug should have a rapid onset and offset of action, minimal respiratory depression, wide therapeutic window, good reversibility, minimal impact on cognitive function, and should have predictive pharmacokinetics.…”
mentioning
confidence: 99%